Doctor-Diagnosed Arthritis and Self-Reported Physical Health Function Among Middle-Aged and Older Adults With Serious Mental Illness. Issue 11 (November 2019) - Brooks, Jessica M.; Umucu, Emre; Sánchez, Jennifer; Seehusen, Carol; Fortuna, Karen L.; Chiu, Chungyi; Bartels, Stephen J.
Abstract : Abstract: Arthritis is one of the most common chronic conditions in aging adults, with both physical and mental health issues and consequences. However, there is insufficient arthritis research among aging adults with serious mental illness (SMI). This study examined rates of doctor-diagnosed arthritis and its cross-sectional associations with self-reported physical health function among adults aged 50 years and older with SMI. Community-based mental health center participants ( n = 176) reported clinical and sociodemographic data ( e.g., physical health function, sex), whereas diagnostic information ( i.e., arthritis, psychiatric, and medical diagnoses) was retrieved from medical records. Arthritis prevalence was high (43.8%) and had an independent, negative association with physical health function. Findings suggest that arthritis evaluations and intervention services need to be prioritized in middle-aged and older adults with SMI. Future research should focus on further testing arthritis self-management programs and other nonpharmacological psychosocial approaches for arthritis in aging adults with SMI.